2021
DOI: 10.1186/s12959-021-00326-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of direct oral anticoagulants for thromboprophylaxis or treatment of cancer-associated venous thromboembolism: a meta-analysis and review of the guidelines

Abstract: Background Venous thromboembolism (VTE) is a common complication among patients with cancer and is one of the most common causes of increased morbidity and mortality. The use of direct oral anticoagulants (DOACs) for thromboprophylaxis and treatment of cancer-associated venous thromboembolism (CA-VTE) has been evaluated in several randomized clinical trials (RCTs). The aim of this meta-analysis was to assess efficacy and safety of using DOACs for thromboprophylaxis and treatment of CA-VTE and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Another meta-analysis showed that DOACs were linked with a significant reduction in VTE recurrence but with an incremental risk of CRNM. 96 …”
Section: Resultsmentioning
confidence: 99%
“…Another meta-analysis showed that DOACs were linked with a significant reduction in VTE recurrence but with an incremental risk of CRNM. 96 …”
Section: Resultsmentioning
confidence: 99%
“…In Table 1, we described the baseline characteristics of patients that were on DOAC therapy prior to index hospitalization. The median age for patients on DOAC therapy was 69 years [IQR 59-78] years, with a median APACHE III score at 24 hours of 64 [51-78] and Charlson's comorbidity score 4 [5][6][7][8][9][10][11]. Commonest comorbidities included any cancer (N = 291, 52.2%), Diabetes mellitus (N = 189, 33.9%), congestive heart failure (CHF) (N = 183, 32.8%), and chronic pulmonary disease (including COPD, asthma, pulmonary hypertension, interstitial lung diseases) (N = 172, 30.8%).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…8,9 DOACs also benefit the cancer population by reducing the risk of symptomatic VTE and VTE recurrence. 10 Overall, apixaban and dabigatran (but not rivaroxaban) are associated with lower bleeding risk and death when compared to warfarin in patients with heart failure and atrial fibrillation. 11 The doses often need adjustment due to changes in renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the proven efficacy, convenience and patient preference of DOACs compared to LMWHs and VKAs [10][11][12], recommendations for the use of DOACs in cancer patients have also been included in guidelines. DOACs are recommended in cancer patients without renal and/or hepatic impairment, with low risk of bleeding and without genitourinary or gastro-intestinal tumours [13,14]. However, guidelines also acknowledge that the use of DOACs is not without caveats when in combination with anticancer drugs as there are still concerns about the risk of bleeding and drug-drug interactions (DDIs) may occur [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…DOACs are recommended in cancer patients without renal and/or hepatic impairment, with low risk of bleeding and without genitourinary or gastro-intestinal tumours [13,14]. However, guidelines also acknowledge that the use of DOACs is not without caveats when in combination with anticancer drugs as there are still concerns about the risk of bleeding and drug-drug interactions (DDIs) may occur [13,14].…”
Section: Introductionmentioning
confidence: 99%